The News Rhetoric on Gaze War and Its Influence On 2024 US Elections. A Case Study On CNN - Alanazi, Mohammed (Eximia, 2025)
This study aims to explore the relationship between CNN’s rhetorical framing of the Gaza conflict and its potential influence on electoral decision-making. It investigates whether CNN’s emphasis on humanitarian narratives, international responsibilities, or political accountability might polarize or news coverage. By examining the intersection of media narratives, the study sheds light on how global conflicts become focal points in shaping the U.S. political landscape, particularly during election years. This study focuses on CNN, a prominent U.S. news network, and its coverage of the 2023-2024 Gaza conflict, investigating how its framing strategies might influence the 2024 U.S. presidential election